A Novel Configuration of a Microstrip Microwave Wideband Power Amplifier for Wireless Application - Amine Rachakh; El Abdellaoui Larbi; Zbitou Jamal; Ahmed Errkik; Abdelali Tajmouati; Latrach Mohamed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
RF/microwave power amplifier (PA) is one of the components that has a large effect on the overall performance of communication system especially in transmitter system and their design is decided by the parameters of transistor selected. This letter presents a new concept of a wide-band microwave amplifier using scattering parameters that is often used in the radio frequency communication systemas an application of the active integrated antenna[1- 2]. This power amplifier operates from 1.75 GHz to 2.15GHz frequency and it is based on AT-41410 NPN transistor that has a high transition frequency of 10GHz. The proposed Single Stage PA is designed by microstrip technology and simulated with Advanced Design System (ADS) software. The simulation results indicate good performances; the small power gain (S21) is changed between 11.8 and 10dB. For the input reflection coefficient (S11) is varied between -11 and -22.5dB. Regarding the output reflection coefficient (S22) is varied between -13.1 and -18.7dB over the wide frequency band of 1.75-2.15GHz and stability without oscillating over a wide range of frequencies.